Comparative proteomics—network analysis of proteins responsible for ursolic acid–induced cytotoxicity in colorectal cancer cells. Issue 3 (March 2017) - Cai, Qiaoyan; Lin, Jing; Zhang, Ling; Lin, Jiumao; Wang, Lili; Chen, Daxin; Peng, Jun
Ursolic acid is a key active compound present in many medicinal herbs that have been widely used in traditional Chinese medicine for the clinical treatment of various cancers. However, the precise mechanisms of its antitumor activity have been poorly understood. To identify the cellular targets of ursolic acid, two-dimensional gel electrophoresis combined with mass spectrometry was performed in this study, which identified 15 proteins with significantly altered levels in protein expression. This demonstrated that ursolic acid–induced cytotoxicity in colorectal cancer cells involves dysregulation in protein folding, signal transduction, cell proliferation, cell cycle, and apoptosis. Corresponding protein regulation was also confirmed by Western blotting. Furthermore, the study of functional association between these 15 proteins revealed that 10 were closely related in a protein–protein interaction network, whereby the proteins either had a direct interaction with each other or were associated via only one intermediary protein. In this instance, the ATP5B/CALR/HSP90B1/HSPB1/HSPD1-signaling network was revealed as the predominant target which was associated with the majority of the observed protein–protein interactions. As a result, the identified targets may be useful in explaining the anticancer mechanisms of ursolic acid and as potential targets for colorectal cancer therapy.